2018
DOI: 10.1021/acs.cgd.8b00988
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Growth of Bimetallic Oxides CuMnO2 with Tailored Valence States for Optimum Electrochemical Energy Storage

Abstract: Bimetallic oxides ABO x (x = 2, 3, and 4) with multiple lattice sites have shown numerous properties, blossoming into diverse applications, while regulating the valence state at the A or B site usually causes a dramatic change in the crystal structure, giving rise to uncertainties in comprehending the structure–property relationships. Herein, we synthesized bimetallic layered crednerite CuMnO2 with double-coordinate Cu cations at the A site and hexa-coordinate Mn cations at the B site via a cetyltrimethylammo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 47 publications
0
28
0
Order By: Relevance
“…Various morphologies of bimetallic oxides synthesized via different synthetic routes have been reported by many researchers. [59] Das et al, reported an octahedron morphology for CuCo 2 O 4 , synthesized via ethylenediaminetetraacetic acid (EDTA) assisted hydrothermal approach that is most suited for supercapacitor application. The electrochemical studies on the obtained single-crystalline CuCo 2 O 4 octahedron with a surface area of 61.97 m 2 g À 1 , revealed the specific capacity of 989 C g À 1 at 5 mV s À 1 .…”
Section: Co-based Bimetallic Oxidesmentioning
confidence: 99%
“…Various morphologies of bimetallic oxides synthesized via different synthetic routes have been reported by many researchers. [59] Das et al, reported an octahedron morphology for CuCo 2 O 4 , synthesized via ethylenediaminetetraacetic acid (EDTA) assisted hydrothermal approach that is most suited for supercapacitor application. The electrochemical studies on the obtained single-crystalline CuCo 2 O 4 octahedron with a surface area of 61.97 m 2 g À 1 , revealed the specific capacity of 989 C g À 1 at 5 mV s À 1 .…”
Section: Co-based Bimetallic Oxidesmentioning
confidence: 99%
“…In the last few decades, there has been a renewed interest in the research on the CuMnO 2 material due to its an exceedingly rich spectrum of potential applications. As a p-type semiconductor [5][6][7], electrode material [8], CuMnO 2 has also been examined regarding photocatalytic activities for hydrogen production or hydrogen storage [9][10][11], oxygen storage [12,13], energy storage [14,15] as well as in the context of multiferroic peculiarities [16]. Remarkably, by the use of a hydrothermal method, nanoparticles with diameters of 50 -100 nm [6], or nanowires [15], can be obtained.…”
Section: Introductionmentioning
confidence: 99%
“…The most natural method of preparing different morphologies of nanoparticles is that which can modify condition of reaction, e.g., by varying factors such as precursor solution and its concentration, reaction temperature, reaction time and pH value of the solvents. A successful synthesis upon changes of reaction condition has been documented for delafossite CuGaO 2 [27] or for crednerite CuMnO 2 [15,28]. Fu et al [15] showed that the valence states of samples consisting of Cu 1+ , Cu 2+ , Mn 2+ and Mn 3+ are possibly adjusted varying reaction temperatures.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations